A COMPARATIVE STUDY ON SURFACE CHANGES BETWEEN COMPOSITE VENEER AND ACRYLIC RESIN USING BATTERY-OPERATED TOOTHBRUSH AND MANUAL TOOTHBRUSH - Fabian, Danganan Calvin D.; Gonzales, Epryl Maecel P.; Latoza, Llane Ronimee E.; Yambao, Kristine Dianne G.; L., Meliza Chanelle; Wong, Shirley S. (International Journal of Psychosocial Rehabilitation, 2020)
Early forms of toothbrush have been in existence since 3000 BC. Several changes have happened since then, it has evolved from a ‘chew stick’, into a bristle toothbrush, then a battery-operated toothbrush. Tooth brushing has been our primary way of cleaning the oral cavity and its structures to maintain good oral hygiene. However, prolonged brushing can be abrasive to one’s existing restoration and prosthesis increasing the surface roughness, leaving the resins vulnerable to damage and plaque accumulation. This study aims to evaluate the effect of tooth brushing using a manual toothbrush and a battery-operated toothbrush to the surface roughness of composite resin restorations and denture base acrylic resin. Composite specimens and denture base acrylic specimens showed varying wear and surface roughness with several variables taken into consideration such as brushing force, brushing stroke, dentifrice, type of bristle, and type of toothbrush used. The expected result is that the specimens brushed using the battery-operated toothbrush with applied toothpaste will have greater wear and surface roughness.